Differential Function of a Novel Population of the CD19+CD24hiCD38hi Bregs in Psoriasis and Multiple Myeloma - Joanna Bartosińska; Joanna Purkot; Agnieszka Karczmarczyk; Michał Chojnacki; Joanna Zaleska; Paulina Własiuk; Norbert Grząśko; Marta Morawska; Adam Walter-Croneck; Lidia Usnarska-Zubkiewicz; Patrycja Zielińska; Krzysztof Jamroziak; et al. (Cells, 2021)
Psoriasis (Ps), an autoimmune disease, and multiple myeloma (MM), a blood neoplasm, are characterized by immune dysregulation resulting from the imbalance between the effector and regulatory cells, including B regulatory (Breg) lymphocytes. Peripheral blood samples from 80 Ps patients, 17 relapsed/refractory MM patients before and after daratumumab (anti-CD38 monoclonal antibody) treatment, 23 healthy volunteers (HVs), and bone marrow samples from 59 MM patients were used in the study. Bregs were determined by flow cytometry using CD19, CD24, and CD38. Intracellular production of interleukin-10 (IL-10) was assessed by flow cytometry after CD40L, LPS, and CpG stimulation. IL-10 serum or plasma concentrations were tested using ELISA method. The percentage of CD19+CD24hiCD38hi Bregs was not different whereas the production of IL-10 in Bregs was significantly higher in Ps patients in comparison with HVs. The percentage of CD19+CD24hiCD38hi Bregs in MM patients was significantly higher than in HVs (p < 0.0001). The percentage of CD19+CD24hiCD38hi Bregs was significantly higher in MM patients with the ISS stage I (p = 0.0233) while IL-10 production in Bregs was significantly higher in ISS stage III (p = 0.0165). IL-10 serum or plasma concentration was significantly higher in Ps and MM patients when compared to HVs (p < 0.0001). Following the treatment with daratumumab the percentages of CD19+CD24hiCD38hi Bregs significantly decreased (p < 0.0003). Here, in the two opposite immune conditions, despite the differences in percentages of Bregs in Ps and MM we have identified some similarities in the IL-10 producing Bregs. Effective treatment of daratumumab besides the anti-myeloma effect was accompanied by the eradication of Bregs.